Pembelajaran Berbasis Projek (Project Based Learning) pada Pengajaran English Drama Appreciation dengan Menggunakan Media Pementasan Drama Berbahasa Inggris "Sangkuriang" - Haryati Sulistyorini (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Abstract: This paper entitled Wisata Sastra pada Pengajaran English Drama Appreciation dengan menggunakan Media Pementasan Drama "Sangkuriang", has a purpose for learners dan teachers in literature to give an assumption that literary criticism could be done not only by using reception theory but also used another model in teaching like Project Based Learning. The Project Based Learning in Engish Drama Appreiation with a play perform, Sangkuriang also has the main purpose to introduce and promote the toursm object of Tangkuban Perahu as the popular tourism object in Indonesia especially in West of Java. This is usually called by travelling literature which also has a function to promote and popular the tourism object. Descriptive qualitative is used to describe the data which is acquired in the project based learning.The result shows that teaching learning in English Drama Appreciation which is done by the project based learning is able to give students in the interpretation on a literary work in a play perform like Sangkuring.